MAILLARD AND CARAMELIZATION REACTIONS IN CONFECTIONERY PRODUCTS - Baiq Afriza Lia Fitri; Murdiah, Murdiah; Baiq Pebriyanti Hidayati (Journal of Innovation Research and Knowledge, 2025)
The Maillard reaction and caramelization are two major non-enzymatic browning reactions that play a vital role in shaping the organoleptic characteristics of sugar-based confectionery. These thermal-induced reactions are responsible for the formation of brown pigments, flavor compounds, and aroma volatiles that define the sensory identity of products such as caramel, toffee, and fudge. This review aims to explore the fundamental mechanisms of both reactions, their dependency on ingredient composition and process conditions, and their contribution to color, flavor, and texture development in confectionery systems. Understanding these reactions is essential for optimizing quality while minimizing risks.